PENGEMBANGAN MEDIA PERMAINAN MONOPOLI BUAH (MOBU) UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN: DEVELOPMENT OF FRUIT MONOPOLY GAME (MOBU) MEDIA TO IMPROVE THE COGNITIVE ABILITIES OF CHILDREN AGED 5–6 YEARS - Jenica Yulia Meintika; Linda Dwiyanti; Veny Iswantiningtyas (Thufuli, 2023)
This study aims to produce fruit monopoly game media (MOBU) that is suitable for use by early childhood. In this study using the type of research and development or often called R & D. The design of this development research uses modifications and the Borg and Gall model. The product validity data analysis technique uses the V formula as Aiken and uses SPSS in field trials (limited trials) and expansion trials. From the results of the validator's assessment, it got a value of more than 0.05 so that the fruit monopoly game media can be said to be very feasible to use. Supported by the results of media trials in terms of convenience and attractiveness, the percentage results are 95%. Therefore, the fruit monopoly game media can be said to be valid and appropriate for use in early childhood learning, especially to improve the cognitive abilities of children aged 5-6 years.